A Preliminary Diagnostic Study on Narrative Writing Skills of Third Grade Students - Nopitasari, Solehah; Sukartiningsih, Wahyu; Hendratno, Hendratno; Mariana, Neni; Puspita, Ari Metalin Ika Puspita (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
This study aims to analyze the narrative writing skills of third-grade elementary students using an initial diagnostic approach. A descriptive qualitative method was employed, with data collected from 25 students through a writing task titled "An Enjoyable Vacation." The analysis revealed that most students had not yet mastered a complete narrative structure, with only 24% able to write a fully developed story. Common issues included limited vocabulary, punctuation errors, and underdeveloped or clichéd story ideas. This research underscores the importance of diagnostic evaluation in designing adaptive, needs-based writing instruction. The findings suggest the necessity of a process-based approach to writing, along with explicit training in both language use and story structure.